ANALISIS STRATEGI BERSAING PT BCT DALAM INDUSTRI BAHAN BAKU OBAT FARMASI - Bonar Jeppry Napitupulu (Journal Of Communication Education, 2016)
ABSTRACT In today’s globalization and borderless market, competitive strategy is essential for the survival and growth of company. To win the competition, a company has to find out, choose and formulated a new strategy, through analyzing internal and external condition of the company and industry. This study analysis the current strategy still suitable to the competition among the company within the industry. Factors that contribute to customers satisfaction, particularly in raw material of pharmaceutical. It’s focuses on the internal and external analysis. The competitive strategy method in this study was based on Generic Porter. The study reveals that the new strategy of PT BCT, is more to focus strategy. With focus strategy, PT BCT will take advantage from higher profit and customers loyalty. Key words: Competitive strategy and Focus strategy